State-Owned Banks Financial Performance: Non-Performing Loans, Liquidity, Interest Rates, And Profitability - Aziz, Khalid Fauzi; Handoyo, Ugroseno Damara Prasadhana; Indra, Muksin Nur (LPPM ISNJ Bengkalis, 2024)
This study aims to analyze the effect of bad debt, liquidity, interest rates, and profitability on the financial performance of Indonesian state-owned banks. The data used are secondary data from published financial reports on the Indonesian Stock Exchange in 2021-2023. The method used is quantitative descriptive. The population of the study was all state-owned banks, namely six issuers. The sampling technique used saturated samples so that the number of samples was the same as the population. The banks used as samples were Bank Rakyat Indonesia, Bank Mandiri, Bank Negara Indonesia, Bank Tabungan Negara, Bank Syariah Indonesia, and Bank Raya Indonesia. The data analysis technique used multiple linear regression with the help of the SPSS program. The study showed that bad debt and profitability negatively affect financial performance. Meanwhile, interest rates and liquidity did not affect financial performance. Theoretically, this study can complement existing theories and be a reference for further research. Practically, this study can be used as a reference for banks in improving their financial performance.